The The Relationship Between Physical Activity and Cardiovascular Levels of Students on the Banjarmasin Riverbanks - Lazuardy Akbar Fauzan; Edwin Wahyu Dirgantoro; Perdinanto Perdinanto; Yakup Nahuay; Abdi Nul Huda (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2026)
Environmental conditions influence physical activity. The environment in which students live significantly influences their physical abilities. Other factors that influence physical fitness include the level of physical activity, nutrition, economic conditions, environmental conditions, community mindsets, and available facilities and infrastructure, including sports facilities. The purpose of this study was to determine the characteristics of physical activity and the level of physical fitness of junior high school students in the Banjarmasin Riverbank area. The method used in this study was descriptive quantitative. The sample in this study was junior high school students in the Banjarmasin Riverbank area. This research instrument used a physical activity questionnaire and a physical fitness test, which included a 1000-meter run for boys and an 800-meter run for girls. The data analysis used in this study was conducted with the SPSS 22.0 application. The study concludes that there is a positive and significant relationship between physical activity and the cardiovascular endurance levels of students in the Banjarmasin Riverbank area. This positive relationship indicates that if students are more active in physical activities, their cardiovascular endurance will also improve.